Improving prognosis in coronary heart disease patients after coronary bypass surgery - E. V. Shlyakhto; A. V. Panov; M. L. Gordeev; B. A. Tatarsky; A. A. Totolyan (Кардиоваскулярная терапия и профилактика)
The article contains present and possible promising methods for improving prognosis in coronary heart disease (CHD) patients after coronary bypass surgery (CBS). Increasing CBS rates in Russia requires active implementation of methods improving short and long-term prognosis. Bypass stenosis mechanisms involve chemokine system. Secondary CHD prevention includes risk factor control, anti-aggregant, beta-adrenoblocker, lipid-lowering, and ACE inhibitor therapy. Recent studies have demonstrated beneficial w-3 polyunsaturated fatty acid role in improving surgery outcomes and prognosis in CHD patients.